Characteristics of platelet indices, neutrophil-to-lymphocyte ratio and erythrocyte sedimentation rate compared with C reactive protein in patients with cerebral infarction: a retrospective analysis of comparing haematological parameters and C reactive protein. Issue 11 (20th November 2014) - Lee, Jong-Han; Kwon, Kyum-Yil; Yoon, Soo-Young; Kim, Hyon-Suk; Lim, Chae Seung
Abstract : Objective: Elevation of C reactive protein (CRP) is one of the major acute-phase responses following ischaemic or haemorrhagic stroke. This study aims to investigate the associations between platelet indices, neutrophil-to-lymphocyte ratio (NLR) and erythrocyte sedimentation rate (ESR) compared with CRP in patients with cerebral infarction. Setting: The clinical data of patients with cerebral infarction were analysed retrospectively. Participants: We analysed, unduplicated, 516 patients with cerebral infarction (mean age 66.2±12.7, male/female=291/225). Outcome measures: Mean platelet volume (MPV), MPV to platelet count, NLR and ESR were compared with CRP in patients with cerebral infarction in a single institute through Spearman correlation test. Results: There were significant correlations between CRP and MPV (ρ=0.088, p=0.045), NLR (ρ=0.4, p<0.001) and ESR (ρ=0.468, p<0.001) in patients with cerebral infarction. In the male group, NLR (ρ=0.398, p<0.001) and ESR (ρ=0.502, p<0.001) showed significant correlations with CRP. In the female group, CRP showed significant correlations with MPV (ρ=0.17, p = 0.011), NLR (ρ=0.392, p<0.001) and ESR (ρ=0.475, p<0.001). Conclusions: MPV, NLR and ESR showed significant correlation with CRP in patients with cerebral infarction. MPV and NLR are cost-effective and simple parameters that can be attainable by using an automatic haematology analyser. Further well-designed and large-scale prospective studies are warranted to evaluate platelet indices or NLR for monitoring patients with cerebral infarction.